The Drift of Lenin's Convoy in the Laptev Sea, 1937-1938 - Barr, William (ARCTIC, 1980)
As a result of various miscalculations 25 ships underwent an enforced wintering at various points in the Soviet Arctic in the winter of 1937-1938. Among the vessels involved was a convoy of six ships led by the icebreaker Lenin, which spent the winter drifting in the Laptev Sea. Several of the ships were severely damaged by ice pressure, and one ship was crushed and sank. Early in 1938 all superfluous personnel were flown south to Tiksi in an emergency airlift operation. The author presents the first detailed English-language account of this wintering.